The importance of participation in student organizations for soft skills development - Vieira, Francisco Machado Silva Passos (2019)
The importance of developing transversal skills in a student's academic career arises mostly from the new demands of the labor market. Performance and competency management issues in organizations have changed in recent years. Hard skills used to be fundamental, but the paradigm has changed, and today something different is needed that keeps people in line with the demands of the world we live and work in, and increasingly facilitates the necessary interaction with other people. This is so called soft skills. As such, it is necessary to understand the level of adaptability of the higher education teaching model in view of this whole new labor market paradigm. Students' participation in Student Organizations enables them to further develop the skills sought by employers by engaging in different challenges and activities and especially through the level of commitment given to each of their responsibilities. This research aims to gather theoretical grounding on the topics described above and at the same time, through an online survey, obtain a personal opinion of several individuals with experience and active participation in student organizations, during their academic course. Thus, it has become evident, both through literary review and data collection, that participation in Student Organizations is increasingly important and should be valued by employers, given their ability to further develop than the teaching model of higher education, the skills required by the labor market.